Strategi Digital Marketing Dalam Meningkatkan Penjualan Di Goory Coffee And Eatery - Dewi, Ni Luh Ayu Ciptasari; Wiranatha, Anak Agung Putu Agung Suryawan; Yoga, I Wayan Gede Sedana; Sadyasmara, Cokorda Anom Bayu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
This study aims to identify key success factors, formulate strategic recommendations to increase sales, and evaluate the implementation results of digital marketing strategies at Goory Coffee and Eatery. Goory Coffee and Eatery faces challenges of fluctuating sales and suboptimal digital marketing strategies. Benchmarking was used to assess the effectiveness of the current digital marketing strategies. The RACE framework (Reach, Act, Convert, Engage) combined with SWOT analysis was employed to evaluate internal and external factors influencing digital marketing. Recommended strategies include enhancing the creativity of social media content, optimizing customer loyalty programs, and utilizing digital advertising more effectively. The findings indicate that marketing through Instagram and TikTok successfully increased audience reach and consumer engagement, contributing to a revenue increase of IDR 49,269,623 per month. However, challenges remain, such as the suboptimal repeat order strategy and the underutilization of paid advertisements (ads).